The Development of Islamic Religious Education Learning Materials on Environmental Issues Using Scientific Verses and the Think–Talk–Write (TTW) Strategy (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to develop Islamic Religious Education (IRE) teaching materials on environmental issues with scientific qur’anic verses using the Think Talk Write (TTW) strategy at SMA Negeri Aceh Utara. This research employs research and development methods provide valid, practical, and successful educational resources. The findings indicate that the created instructional materials significantly improve student learning outcomes. Students who use this teaching material exhibit better learning outcomes compared to before. This teaching material can serve as a learning resource in schools with students of varying abilities. The material is designed by integrating scientific process skills into the learning content, enabling students to better understand environmental concepts. The TTW strategy facilitates systematic thinking and opinion exchange among students in solving environmental problems. The findings indicate that the developed teaching material can improve student learning outcomes classically. Therefore, this instructional instrument can serve as an alternative for IRE learning at SMA Negeri Aceh Utara.